Pengaruh good corporate governance terhadap profitabilitas dengan pengungkapan tanggung jawab sosial perusahan sebagai variabel intervening pada perusahan LQ 45 yang terdaftar di Bursa Efek Indonesia - Havit Kurniawan Purnama; Sri Trisnaningsih (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2020)
The research aims to determine the effect of GCG (institutional ownership, managerial ownership, board of commissioners, audit committee) and profitability on CSR disclosure in LQ45 companies in 2016 - 2018. Research data were obtained from the IDX (Indonesia Stock Exchange). This type of research is a quantitative research method. The population in the study consisted of LQ 45 companies listed on the Indonesia Stock Exchange in 2016 - 2018 were 56 companies while the samples that met the criteria were 37 companies. The author uses path analysis, multiple regression analysis, as data analysis.